COVID-19 exacerbates unequal food access. (September 2021) - Kar, Armita; Motoyama, Yasuyuki; Carrel, Andre L.; Miller, Harvey J.; Le, Huyen T.K.
Abstract: Inequality to food access has always been a serious problem, yet it became even more critical during the COVID-19 pandemic, which exacerbated social inequality and reshaped essential travel. This study provides a holistic view of spatio-temporal changes in food access based on observed travel data for all grocery shopping trips in Columbus, Ohio, during and after the state-wide stay-at-home period. We estimated the decline and recovery patterns of store visits during the pandemic to identify the key socio-economic and built environment determinants of food shopping patterns. The results show a disparity: during the lockdown, store visits to dollar stores declined the least, while visits to big-box stores declined the most and recovered the fastest. Visits to stores in low-income areas experienced smaller changes even during the lockdown period. A higher percentage of low-income customers was associated with lower store visits during the lockdown period. Furthermore, stores with a higher percentage of white customers declined the least and recovered faster during the reopening phase. Our study improves the understanding of the impact of the COVID-19 crisis on food access disparities and business performance. It highlights the role of COVID-19 and similar disruptions on exposing underlying social problems in the US. Highlights: We studied changes in food access using observed food shopping travel during COVID-19. Big-box stores had the highest decline in visitors during lockdown and the fastest recovery in the reopening phase. Dollar stores had the lowest decline during lockdown. We found smaller changes in visits to stores in low-income areas. A higher percentage of low-income customers was associated with lower traffic decline to a store during lockdown. Stores with a higher percentage of white customers declined the least and recovered faster during the reopening phase.